The Trade Response to Global Downturns : Historical Evidence - Freund, Caroline (2012)
The author examines the impact of historical global downturns on trade flows. The results provide insight into why trade has dropped so dramatically in the current crisis, what is likely to happen in the coming years, how global imbalances are affected, and which regions and industries suffer most heavily. The author finds that the elasticity of global trade volumes to real world GDP has increased gradually from around 2 in the 1960s to above 3 now. The author also finds that trade is more responsive to GDP during global downturns than in tranquil times. The results suggest that the overall drop in real trade this year is likely to exceed 15 percent. There is significant variation across industries, with food and beverages the least affected and crude materials and fuels the most affected. On the positive side, trade tends to rebound very rapidly when the outlook brightens. The author also finds evidence that global downturns often lead to persistent improvements in the ratio of the trade balance to GDP in borrower countries.